The Personality of the Hadith Scholar and Its Importance to Psychology - BADRI, KHAIRUL NIZAM BIN ZAINAL (Al-Qalb : Jurnal Psikologi Islam, 2021)
The field of personality is often became a concern to psychologists who want to look at human behavior both from positive and negative angles. In other words, personality has a relationship with behavioral development potential. Personality has a direct relationship with the field of psychology. One of the most important definitions of personality is individual differences according to characteristic patterns such as thoughts, feelings and actions. Personality traits are biological while personality values are environmental products influenced by culture, education and life. In the study of modern psychology, thought-based traits that are in the cognitive domain are higher than emotional traits in relation to values. In the tradition of Islamic science, there is a special traits, which is the yardstick of superior personality; that is, Al-‘Adalah or is called adil (fairness). Related to the trait of adil is the trait of dhabit (strong memory). A qualitative study using this library approach seeks to trace the properties possessed by hadith scholars, who once inspired the West to apply those attributes in their intellectual work. Studies have found that these properties have unique characteristics because of their ability to integrate ontological, epistemological and axiological dimensions and also balance the role of cognitive and affective domains in human beings that direct human physiological and psychological behavior in a positive direction. In conclusion, the development of good potential will result in an authoritative and noble personality.